Theoretical and experimental study of plasmon oscillation dispersion in Si and Ge crystals - Z.A. Isakhanov; B.E. Umirzakov; G.T. Imanova (Optical Materials: X)
Plasma fluctuation dispersion has been theoretically and experimentally studied in monocrystal samples of Si (111) and Ge (111). It has been shown that the dispersion depends on crystallographic orientations of materials under study. In this work, the dispersion effects in the CLEE spectra, which manifest themselves in bulk samples of Si and Ge, have been studied. The loss energy electron was studied by the CLEE method upon their reflection from Si(111) and Ge(111) at different angles of incidence of the electron beam on the surface. Calculation of the total electron energy loss with formula (5) shows that the form of the CLEE spectrum of primary electrons depends on the nature and magnitude of the electron density in a given direction and is in satisfactory agreement with the experimental data. Thus, the theoretical and experimental results show that in the case of single-crystalline Si and Ge, with increasing k, the values of the bulk plasma oscillation increase by 2–3 eV.